Effects of a Commercial Formulation of Cypermethrin used in Biotech Soybean Crops on Growth and Antioxidant Enzymes of Freshwater Algae - Sáenz, María Elena (2012)
Commercial formulation of pyrethroid insecticide Cypermethrin used in soybean crops was very toxic to four freshwater algae studied causing harmful effects on algal growth and antioxidative defense system level. Recovery from exposure would be seriously affected since Cypermethrin commercial formulation caused algicidal effects. Antioxidant enzymes were significantly stimulated at concentration below LOEC values derived from algal growth inhibition test. The activation of antioxidant enzymes could be used as sensitive biomarkers for early warning of the action of pyrethroid insecticides. This concentration was below measured field concentration of Cypermethrin (0.092 mg Cyp/L) in a stream from a soybean crop area, indicating enzymatic biomarkers could anticipate adverse actions on recovery. Concentrations of commercial formulation which caused algistatic effects on P. subcapitata produced an inhibition of CAT and GR activity, showing oxidative stress damage. The use of insecticides in large areas for growing soybeans is discussed, as toxicity to green algae of formulated Cypermethrin is higher than the others two widely used insecticides, Endosulfan and Chlorpyrifos.